Pengaruh Model Pembelajaran Kooperatif dan Kreativitas Belajar Siswa terhadap Pemahaman Konsep Matematika - Ida Oktavia (JKPM (Jurnal Kajian Pendidikan Matematika), 2015)
The purpose of this study was to determine: (1) the effect of cooperative learning model in understanding mathematical concepts, (2) the effect of learning creativity  on   mathematical concepts understanding, and (3) the effect of the interaction model of cooperative learning and learning creativity in understanding mathematical concepts. The method used is an experimental method with 2-way ANOVA analysis. These samples included 60 students grade seventh at Junior High School in Cengkareng, West Jakarta. Before test the hypothesis, testing requirements of data analysis consisted of the normality test and homogeneity test. Results of research and data analysis can be concluded: (1) there is the effect of cooperative learning model in understanding mathematical concepts, (2) there is an effect of learning creativity on  understanding mathematical concepts, and (3) there is no interaction effect of cooperative learning and creativity learning in understanding mathematical concepts. Based on the conclusions, it’s suggested that teacher's are demanded to explore all the students’ potential and creativity. In addition, teachers need to use systematic and appropriate learning models.